MACHINE PROCESSING, COOLING, AND MILK PACKAGING WITH 3-IN-1 INTEGRATED PROCESS SYSTEM - Pratama, Yan Dwi; Arimbi, Niken Sari Kiss; Hidayat, Muhammad Sefriza Toriq; Anggoro, Fajar Septiawan Dwi; Khalifah, Aisyah Nur; Budijono, Agung Prijo (AIBPM Publisher, 2018)
The purpose of this study is to provide solutions to problems that exist in SMEs Cow Milk Momoo, especially the problem of production process that the process is still using the traditional way and the tool is still relatively simple.The method used is to utilize Temperature Controller, Motor Wiper, and Heat Exchanger technology which is soaked in water in Processing machine, cooling, and packing of Cow Milk. The expected result is the increasing of productivity and efficiency of production process so that productivity of SME Cow Milk can be increased 2 times fold which initially yields an average of 100 liters of Cow Milk / day can produce up to 200 liters of Cow Milk / day